2021
DOI: 10.52082/jssm.2021.133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chair-Based, Low–Load Elastic Band Resistance Training on Functional Fitness and Metabolic Biomarkers in Older Women

Abstract: Strength training can improve myriad health parameters in elderly cohorts. Although potentially more appropriate for the elderly, low-load resistance training protocols have been less investigated. We aimed to examine the effects of 12 weeks of chair-based, low-load resistance training with elastic band (EBT) on functional fitness and metabolic biomarkers in older women. One hundred sixty-eight women were allocated randomly to an elastic band resistance training (EBT, n = 86, 75.7 ± 8.9 years, 71.3 ± 12.2 kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(63 citation statements)
references
References 65 publications
(67 reference statements)
3
58
1
1
Order By: Relevance
“…The lipidic profile of our older women improved in all variables, GL (%), TC (%) and TG (%) after ME with similar outcomes to other studies with the same or different type of exercise [7,10,11,[21][22][23][24][25][26].…”
Section: Discussionsupporting
confidence: 83%
“…The lipidic profile of our older women improved in all variables, GL (%), TC (%) and TG (%) after ME with similar outcomes to other studies with the same or different type of exercise [7,10,11,[21][22][23][24][25][26].…”
Section: Discussionsupporting
confidence: 83%
“…Muscle weakness plays a major role in the pathogenesis of many diseases of the knee such as osteoarthritis (OA), even in the early stages of the disease; therefore, emphasis should be laid on the strengthening of the quadriceps muscles. Elastic resistance training could be an effective intervention to improve muscle strength, especially during a home exercise program when individuals such as an elderly who may not be able to attend the rehabilitation center for strength training [49,50]. Since the current study demonstrated a significant change in the strength of the quadriceps femoris muscle after 4 weeks of strength training with elastic resistance, it may reduce the treatment costs and rehabilitation time for patients as well as the therapist.…”
Section: Discussionmentioning
confidence: 82%
“…At first glance, these results are unexpected, as the exercise program was aligned with current recommendations (Garber et al, 2011;Cadore et al, 2014;Fragala et al, 2019;Izquierdo et al, 2021) and contained all the necessary stimuli, such as training in repetition ranges from 8 to 12, fast movements and recommended training intensities from moderate to demanding, all which were found to produce positive effects on physical fitness, as well as its components, in older adults (Bemben et al, 2000;Hunter et al, 2001;Kalapotharakos et al, 2005;Richardson et al, 2019;Herda et al, 2020). Furthermore, the usage data also show that the exercise frequency was well within in a range that should be able to produce effects, since even one or two sessions per week have been proven able to do this (Taaffe et al, 1999;Richardson et al, 2019;Jungreitmayr et al, 2021;Stojanović et al, 2021). While neither the frequency of use nor the composition of the program can be considered a reason for the lack of effect on lower body strength and handgrip strength, the testing procedure itself as well as the uncertainty whether the participants have reached the appropriate exercise intensity (due to the unsupervised mode of the exercise program) remain possible reasons for these results.…”
Section: Discussionmentioning
confidence: 89%
“…To achieve a positive effect on muscle strength, and balance with physical exercise programs, a training frequency of 2–3 times per week is recommended ( Nakamura et al, 2007 ; Carneiro et al, 2015 ; Jungreitmayr et al, 2021 ; Stojanović et al, 2021 ). However, improved overall physical fitness tends to show with higher training frequency ( Nakamura et al, 2007 ; Yang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation